Morphogenesis of sensory organ and feeding behavior of the Sultan Fish, Leptobarbus Hoevenii in Early Life Stage - Au, Hsein Loong (2020)
Knowledge on the development in morphology, sensory systems, and behavioural changes with growth in larval fish is essential to provide insight to the fish ecological needs, and contribute to improve the larval rearing techniques. Knowledge on the major sensory system (visual, chemical [olfaction and gustation], or mechanical [water movement detection]) that being relied by the juvenile fish to detect prey for feeding is also important to optimize the feeding protocols in the farming operation. Sultan fish, Leptobarbus hoevenii is a high value freshwater fish for aquaculture in some Southeast Asian countries, including Malaysia and Thailand. However, information on its larval development and sensory-mediated feeding behaviour at early juvenile stage is still not available. Therefore, the present study was conducted. In Experiment 1, the artificially reproduced L. hoevenii larvae were used to examine its morphology and sensory systems, and behavioural changes with growth. At newly hatched, the larval mouth and anus were not opened. The eyes were not pigmented but the pineal organ was formed. Otoliths were observed in otic vesicle, a pair of free neuromast was found behind the eye, but the olfactory epithelium was not differentiated. The larvae were capable to swim in vertical posture and swam actively during daylight (motionless at night). At 3 days post hatching (dph), the larval eyes were pigmented and retinal tapetum was formed, free neuromasts were found at trunk, first taste bud was found in the oral cavity, and pectoral fin buds were formed. The larval mouth and anus were opened. The larvae swam horizontally, and the first exogenous feeding commenced. At 5 dph, the yolk sac was completely absorbed and the retinal rod cells were formed. At 7 dph, the notochord was fully flexed. At 15 dph, the inner ears were calcified and fully developed. At 30 dph, the olfactory organs were fully developed and canal neuromasts were formed. The fish attained similar number of fin spines and rays with the adults; the fish has turned juvenile at this stage. The rapid development in morphology, sensory systems and behavioural changes with growth in the L. hoevenii larvae appears to facilitate them to adapt and survive in the wild, especially when they swift habitats. In Experiment 2, the major sensory system that being relied by the L. hoevenii early juveniles (total length - TL 2.97 cm) to detect preys for feeding was determined. Feeding experiments with four test conditions were designed to selectively prevent the fish from detecting the prey by their visual, mechanical or/and chemical sense(s). These factors were: 1) visual obstruction – feeding experiment in the dark condition, 2) free neuromasts (mechanoreceptors) ablation by the streptomycin treatment, 3) chemoreceptor masking by the Moina juice, 4) presentation of live or frozen Moina as feed. The live Moina would stimulate fish through vision, chemo- and mechano- receptors while dead Moina does not stimulate mechanoreceptors. The ingestion ratio of the L. hoevenii early juveniles was significantly (P < 0.05) higher in the light condition (92.9 – 99.1%) than in the dark condition (1.8 – 11.9%), regardless of the mechano- or/and chemo-receptor intact or ablated fish. In the dark condition, the mechano- or/and chemo- receptor intact or ablated fish were able to ingest small amount of Moina. Therefore, it was confirmed that the L. hoevenii early juveniles are highly depending on vision to detect preys for ingestion, while the contribution of the mechano- and chemo-reception is small. Marine fish larvae inhabiting clear oceanic waters are primarily visual feeders, while larval non-visual feeding is very common in freshwater species, and it is likely important for feeding in the turbid estuaries and tropical rivers, and also at night. This study first reported the visual-mediated feeding in a freshwater fish species. This finding is also supported by the L. hoevenii brain morphological pattern in which it has a large optic tectum.